2005
DOI: 10.1111/j.1365-2710.2005.00633_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Clearance rates of cerivastatin metabolites in a patient with cerivastatin-induced rhabdomyolysis

Abstract: We report on a patient who developed acute rhabdomyolysis after taking cerivastatin. A 74-year-old hypercholestrerolaemic woman taking cerivastatin (0.15 mg/day) for 22 days complained of general muscle weakness and muscle pain. Her serum creatinine phosphokinase level was 19,190 IU/L. Serum myoglobin was over 3000 ng/mL. Serum concentration of cerivastatin at 6 h after taking the last dose (0.15 mg) was 8062.5 ng/L, which was almost 5.7 times higher than that of normal persons. The serum concentration of ceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…One of the novel exonic CYP2C8 variants, V472 fs L494 which results in a modification of the C-terminus, can be expected to exhibit low metabolic activity in vivo because of poor heme incorporation and thus a defective protein. Consequently, carriers of this variant might be expected to experience higher cerivastatin plasma concentrations, as previously reported for the truncated CYP2C8 * 5 variant [32] - which was not found in this study. Allele frequencies of SNPs for CYP2C8 * 3 and CYP2C8 * 4 indicated a slightly lower prevalence in the patient population compared to published MAFs or haplotype frequencies in Caucasian populations, but a statistical analysis could not be performed due to the lack of an appropriate control group.…”
Section: Discussionsupporting
confidence: 62%
“…One of the novel exonic CYP2C8 variants, V472 fs L494 which results in a modification of the C-terminus, can be expected to exhibit low metabolic activity in vivo because of poor heme incorporation and thus a defective protein. Consequently, carriers of this variant might be expected to experience higher cerivastatin plasma concentrations, as previously reported for the truncated CYP2C8 * 5 variant [32] - which was not found in this study. Allele frequencies of SNPs for CYP2C8 * 3 and CYP2C8 * 4 indicated a slightly lower prevalence in the patient population compared to published MAFs or haplotype frequencies in Caucasian populations, but a statistical analysis could not be performed due to the lack of an appropriate control group.…”
Section: Discussionsupporting
confidence: 62%
“…The authors concluded that the 475delA polymorphism, which results in a frameshift and premature protein truncation, was the putative polymorphism causing decreased CYP2C8 metabolizing enzyme activity. In a subsequent analysis, the authors evaluated the cerivastatin metabolite ratios in this patient’s serum, and found the ratio of M-23:M-1 to be lower than in control patients [49]. This finding suggests that decreased metabolism of cerivastatin was evident in this patient, and this may be due to CYP2C8 gene polymorphisms, as previously discussed.…”
Section: Hmg-coa Reductase Inhibitorsmentioning
confidence: 60%
“…As cerivastatin-induced rhabdomyolysis, and more generally statin-induced rhabdomyolysis, is associated with elevated plasma concentration of statins and their active metabolites [10], the reduction in uptake of statins by OATP1B1 variants is expected to lead to higher cerivastatin exposure and an increased risk of rhabdomyolysis. The V174A variant has been associated with an increased risk of simvastatin-induced [5] myopathy and cerivastatin-induced [6] rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of substrate and reaction times were selected to be in the linear range of transport. The cerivastatin concentration is also clinically relevant [10,11]. …”
Section: Methodsmentioning
confidence: 99%